Conservation Policy, Indigeneity, and Changing Traditional Hunting Practices in West Papua - Fatem, Sepus M.; Runtuboi, Yubelince Y.; Fisher, Micah R.; Sufi, Yafed; Maryudi, Ahmad; Sirimorok, Nurhady (Forestry Faculty, Universitas Hasanuddin, 2023)
Regional governments are increasingly developing conservation policy initiatives that are framed alongside the empowerment of Indigenous Peoples. This paper examines the case of Tambrauw, West Papua, that set out to establish one of the first ever Conservation Regencies in Indonesia. To understand the implications of conservation policy developments, we explored from an environmental justice perspective the ways that one of the most important forest-based activities of local communities – hunting – has changed in recent years. Data was collected using qualitative methods of participatory observation and interviews between 2015-2018 across three Tambrauw districts. The study shows how policy changes are increasing clashes between local hunters and conservation officials. This has implications for broader issues of conservation policy and local livelihoods, and sheds light on the more recent trend of foregrounding Indigenous identity in forest management. Although on the face of it the emergence of conservation regencies represents a trend in downscaling authority to empower local communities, findings shows that place-based and more locally responsive policies need to be established to address emerging conflicts that can also meet broader conservation outcomes.